The State-of-the-Art of Patient Portals: Adapting to External Factors, Addressing Barriers, and Innovating - Reynolds, Tera L.; Cobb, Jared Guthrie; Steitz, Bryan D.; Ancker, Jessica S.; Rosenbloom, S. Trent (Applied Clinical Informatics, 2023)
Background and Objective Recent external factors—the 21st Century Cures Act and the coronavirus disease 2019 (COVID-19) pandemic—have stimulated major changes in the patient portal landscape. The objective of this state-of-the-art review is to describe recent developments in the patient portal literature and to identify recommendations and future directions for the design, implementation, and evaluation of portals.Methods To focus this review on salient contemporary issues, we elected to center it on four topics: (1) 21st Century Cures Act's impact on patient portals (e.g., Open Notes); (2) COVID-19's pandemic impact on portals; (3) proxy access to portals; and (4) disparities in portal adoption and use. We conducted targeted PubMed searches to identify recent empirical studies addressing these topics, used a two-part screening process to determine relevance, and conducted thematic analyses.Results Our search identified 174 unique papers, 74 were relevant empirical studies and included in this review. Among these papers, we identified 10 themes within our four a priori topics, including preparing for and understanding the consequences of increased patient access to their electronic health information (Cures Act); developing, deploying, and evaluating new virtual care processes (COVID-19); understanding current barriers to formal proxy use (proxy access); and addressing disparities in portal adoption and use (disparities).Conclusion Our results suggest that the recent trends toward understanding the implications of immediate access to most test results, exploring ways to close gaps in portal adoption and use among different sub-populations, and finding ways to leverage portals to improve health and health care are the next steps in the maturation of patient portals and are key areas that require more research. It is important that health care organizations share their innovative portal efforts, so that successful measures can be tested in other contexts, and progress can continue.
Keywords: patient portals; 21st Century Cures Act; COVID-19; proxy portal access; digital health disparities